2009
DOI: 10.1002/jor.20982
|View full text |Cite
|
Sign up to set email alerts
|

Relative contributions of mechanical degradation, enzymatic degradation, and repair of the extracellular matrix on the response of tendons when subjected to under‐ and over‐ mechanical stimulations in vitro

Abstract: Tendon response to mechanical loading results in either homeostasis, improvement, or degeneration of tissue condition. In an effort to better understand the development of tendinopathies, this study investigated the mechanical and structural responses of tendons subjected to under-and over-stimulations (1.2% and 1.8% strain respectively, 1 Hz). The objective was to examine three sub-processes of tendon response: mechanical degradation, enzymatic degradation, and repair of the extracellular matrix. We subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 23 publications
0
20
1
Order By: Relevance
“…35 Cousineau-Pelletier and Langelier demonstrated that using stimulation of intermediate amplitude (avoiding over-and under-stimulation), degradation can be minimized. 36 While our findings suggest a weak dose-response relationship between load magnitude and mechanical properties, this did not reach statistical significance, suggesting that load magnitude may be less important than the conditioning duration. Conditioning at higher load magnitudes (e.g., 5 N and 10 N per TEC segment) was not possible because of motor overheating.…”
contrasting
confidence: 49%
“…35 Cousineau-Pelletier and Langelier demonstrated that using stimulation of intermediate amplitude (avoiding over-and under-stimulation), degradation can be minimized. 36 While our findings suggest a weak dose-response relationship between load magnitude and mechanical properties, this did not reach statistical significance, suggesting that load magnitude may be less important than the conditioning duration. Conditioning at higher load magnitudes (e.g., 5 N and 10 N per TEC segment) was not possible because of motor overheating.…”
contrasting
confidence: 49%
“…Moreover, the shape and dimensions of the curve will vary with the addition of cellular activity (the processes of repair and enzymatic degradation) which the authors will try to evaluate in future studies just as has been done with strain-controlled stimulation. 9 Those studies will be more complex and will require more advanced modeling techniques, because other variables such as the incorporation of rest time will eventually need to be included. FIGURE 9.…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of this method was noticed in a study conducted by the authors' group on live tissues under very low amplitude mechanical stimulation. 9 The second factor is contamination which was avoided by using good practices in tissue culture as well as antibiotics/antimycotics. The final factor is time which can modify the tissue via thermodynamics.…”
Section: Discussionmentioning
confidence: 99%
“…This would be a necessary analysis in a future in vivo study, to assess the effect of cellularity on graft degradation and remodeling. 57 In conclusion, making multiple short slits in an intrasynovial tendon decellularized for potential allograft use enhances the penetration and survival of seeded cells. The process does not change the tendon's tensile stiffness.…”
Section: Cell Repopulation In Tendon Allograft 571mentioning
confidence: 98%